Perancangan UI/UX pada Aplikasi Taspen Otentikasi Berbasis Mobile Dengan Menggunakan Metode Design Thinking - Arif Febrian; Fahrobby Adnan; Januar Adi Putra (Puslitbang Sekawan Institute Nusa Tenggara, 2023)
Along with the development of today's technology, the role of information system services becomes very important in overcoming various kinds of community problems effectively and efficiently. Taspen Authentication is an example of an information system service aimed at retired civil servants (PNS). However, there are still problems with the taspen authentication application that make it difficult for some users to run it. The majority of users of this application are the elderly group aged ≥ 60 years and have limited physical function and cognitive function. Based on the results of initial observations and interviews of researchers involving Taspen and several users in the elderly category, it was found that there were problems that caused the lack of efficiency in using the taspen authentication application in terms of UI/UX. The purpose of this research is to design a UI/UX that suits the needs of users, especially the elderly, using the design thinking method. In addition to using the design thinking method, researchers also use User Experience Questionnaire (UEQ) at the testing stage to determine the feasibility of the application prototype that has been designed and get feedback from the target user. The results of the study show that the new interface design provides a very good user experience as evidenced by the results of the 6 UEQ scales which are of excellent value. So the researcher concludes that the UI/UX design on the taspen authentication application that uses the design thinking method is able to provide a description of user needs, especially for the elderly.